In search of pilgrim routes across southern Fife, 1100–1550 - Manson, Bruce F. (The Innes review, 2021)
This study aims to review the evidence for under-studied aspects of pilgrimage in south and central Fife, the likely routes taken by pilgrims, their overnight accommodation and the changing landscape crossed by these travellers. It focusses in on the tracks, burns, marshes and hospices that lay between the great and better studied centres, such as Dunfermline, Inverkeithing, and St Andrews itself, and tries to draw together the written evidence, the landscape features and the recently researched historical and place-name evidence.